Torticollis as a rare, late complication of VP shunt placement in the pediatric population: a case report - Kalliri, Vasiliki; Krieg, Sandro; El Damaty, Ahmed (Child's nervous system, 2024)
The placement of a ventriculoperitoneal (VP) shunt is a common neurosurgical, pediatric procedure with various, well-documented complications occurring both in the immediate postoperative course of the procedure and at later stages. Pediatric patients need frequent revision surgeries due to body growth as well as implant failure over the course of the years. We report a rare case of a 12-year-old patient, presenting with torticollis, 11 years after the initial placement of a VP shunt. The peripheral tube had to be surgically removed due to the severe movement limitation of the cervical spine area and the tilting of the head. This is the fourth case known to be reported with this rare complication. The calcification of the tube and the formation of a rigid scar tissue along the shunt tube, combined with the body growth, are the suspected mechanisms of this mechanical malfunction of the VP-shunt. The complication could be efficiently addressed through the surgical replacement of the peripheral tube and the transection of the scar tissue in the neck area.